You are on page 1of 4

# Algebra 2

Name___________________________________

## Inverse Function Matching

Find the inverse of each function.
1) g( x) =

3x + 3
5

3) f ( x) = - x - 4

5) g(n) = -n - 5

7) f ( x) =

-x - 5
2

5
4

2) g(n) =

2n - 8
5

4) f (n) = -3n - 12

6) g( x) =

-3 x - 12
4

8) h( x) =

-12 + 3 x
4

12 - x
3

9) h( x) = 2 - x

10) f ( x) =

11) f ( x) = x - 2

12) f ( x) = -2 x + 6

13) g( x) =

2+x
2

14) g(n) = n + 4

## Worksheet by Kuta Software LLC

-1-

v n2j0c1M4y GKruStCa^ SSUoEfttswmaLrpea PLGLXC[.i a OABlsl_ xr]iYg]hntgsD er^eWsgedrBvNehda.j z zMoaDdjeL TwiiitfhN zIqnpfFiKnZiQtpeu hAalbg^eAbzrbai q2\.

15) f ( x) =

-5 - 2 x
5

16) h( x) = - x +

17) f (n) =

5n + 5
3

18) g( x) = -

3
7

19) g( x) = - x -

9
7

5
7

10
7

5
4

20) g( x) = -2 + x

21) f ( x) =

5 x + 10
2

22) g( x) = x +

23) g( x) =

5 - 3x
5

24) g( x) =

5
6

5
3

4 + 5x
4

25) f ( x) = x + 1

## Worksheet by Kuta Software LLC

-2-

T [2N0q1R4\ EKKuEtWa^ RSioGfptswFayrdeW xLULVCl.e E rAslulV qrhiagHhOtSsc JrYe`sUe`r`vaeodS.Q Q `MraAdjeF Pw`iAtPhE fIpnsfQicnRiatOe] NAUlvgSeVbVrDap X2B.

Algebra 2

Name___________________________________

## Inverse Function Matching

Find the inverse of each function.
1) g( x) =

3x + 3
5

g -1( x) =

2) g(n) =

-3 + 5 x
3

3) f ( x) = - x - 4

2n - 8
5

g -1(n) =

4) f (n) = -3n - 12

f -1( x) = - x - 4

f -1(n) =

5) g(n) = -n - 5

6) g( x) =

g -1(n) = -n - 5

-x - 5
2

8) h( x) =

f -1( x) = -2 x - 5

5
4

9) h( x) = 2 - x

4
5

h -1( x) = - x +

11) f ( x) = x - 2

2+x
2

-12 - 4 x
3

-12 + 3 x
4

h -1( x) =

10) f ( x) =

4 x + 12
3

12 - x
3

f -1( x) = -3 x + 12

8
5

12) f ( x) = -2 x + 6

f -1( x) = x + 2

13) g( x) =

-12 - n
3

-3 x - 12
4

g -1( x) =

7) f ( x) =

5n + 8
2

1
2

f -1( x) = 3 - x

14) g(n) = n + 4
g -1(n) = n - 4

g -1( x) = 2 x - 2

## Worksheet by Kuta Software LLC

-1-

V ]2h0O1^4n ZKvuOt[aa OSDoxfTtKwsahrmeO PLALiCh.` \ ]AnlJlh GrriGgKhTtis[ qrWe[sTezrKv]esdR.t l oMPamdueh UwEibt`hl lI_nVfAiVn^iDtzeQ sAPl^gce`bZrvae A2a.

15) f ( x) =

-5 - 2 x
5

f -1( x) =

17) f (n) =

-5 x - 5
2

5n + 5
3

f -1(n) =

5
7

16) h( x) = - x +

7
5

h -1( x) = 2 - x

18) g( x) = -

3
7

20) g( x) = -2 + x

7
3

g -1( x) = x +

5 x + 10
2

f -1( x) =

23) g( x) =

5
4

4
5

5
6

22) g( x) = x +

-10 + 2 x
5

5 - 3x
5

g -1( x) =

9
7

g -1( x) = -3 - x

21) f ( x) =

g -1( x) = -2 x

-5 + 3n
5

19) g( x) = - x -

10
7

8
5

5
3
6
5

g -1( x) = -2 + x

24) g( x) =

-5 x + 5
3

4 + 5x
4

g -1( x) =

4x - 4
5

25) f ( x) = x + 1
f -1( x) = x - 1

## Worksheet by Kuta Software LLC

-2-

J i2E0F1T4s zKPuDtqap eSZoyfbt\waaarleO SLaLkCV.F X hAVlTlM ArViRg^hMtxsq EroeFsQedrrvleqdR.H q HMhaydbeF xwziUt_hI KIDnMf]ientiRtpe` GAAlEgsenb^rUaS n2p.